2019
DOI: 10.1177/1556264619826796
|View full text |Cite
|
Sign up to set email alerts
|

Children in Social Research: Do Higher Payments Encourage Participation in Riskier Studies?

Abstract: The MESSI (Managing Ethical Studies on Sensitive Issues) study used hypothetical scenarios, presented via a brief online survey, to explore whether payment amounts influenced Australian children and young people to participate in social research of different sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…The finding that studies involving children paid more than studies involving nonstudent adults and college students is interesting, particularly in light of the ethical debate surrounding research payments to children (Bagley, Reynolds, & Nelson, 2007; Iltis, Matsuo, & DeVader, 2008; Ross, 2005; Wendler, Rackoff, Emanuel, & Grady, 2002). Specifically, there are concerns that children are more susceptible to undue influence from payment, and have limited capacity to understand the requirements of participation and the potential risks of participation (Taplin et al, 2019). However, considering that nearly all of our data came from minimal risk studies and the relatively low payment levels (the highest being USD 120 for a 46.5-hr study across 14 weeks), it is unlikely that child research participants were unduly influenced (Taplin et al, 2019; Wendler et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that studies involving children paid more than studies involving nonstudent adults and college students is interesting, particularly in light of the ethical debate surrounding research payments to children (Bagley, Reynolds, & Nelson, 2007; Iltis, Matsuo, & DeVader, 2008; Ross, 2005; Wendler, Rackoff, Emanuel, & Grady, 2002). Specifically, there are concerns that children are more susceptible to undue influence from payment, and have limited capacity to understand the requirements of participation and the potential risks of participation (Taplin et al, 2019). However, considering that nearly all of our data came from minimal risk studies and the relatively low payment levels (the highest being USD 120 for a 46.5-hr study across 14 weeks), it is unlikely that child research participants were unduly influenced (Taplin et al, 2019; Wendler et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there are concerns that children are more susceptible to undue influence from payment, and have limited capacity to understand the requirements of participation and the potential risks of participation (Taplin et al, 2019). However, considering that nearly all of our data came from minimal risk studies and the relatively low payment levels (the highest being USD 120 for a 46.5-hr study across 14 weeks), it is unlikely that child research participants were unduly influenced (Taplin et al, 2019; Wendler et al, 2002). In addition, research suggests that children are not at greater risk for undue inducement than other populations and that payments can be utilized to increase children’s participation in research without concerns of undue inducement as long as they are age-appropriate (Bagley et al, 2007; Bentley & Thacker, 2004; Taplin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only payments were considered unimportant by the HREC member respondents. The offer of payments to child research participants has been a contentious matter for many HRECs, predominantly because of concerns that children might be coerced by the offer to participate in research in which they would not have otherwise participated (Taplin et al, 2019). A lack of clear guidance on these issues has led some research ethics committees historically to refuse research payments for children (Bagley, Reynolds, & Nelson, 2007) which can then reduce the likelihood of children participating in such research.…”
Section: Important Factors In Considering Research With Childrenmentioning
confidence: 99%
“…This should be analyzed carefully to avoid the possibility of children agreeing to participate in research without wanting to but being tempted by the promise of a reward. A study with Australian children by Taplin et al (2019) reported that children were more likely to participate in the study when payment was offered. A different option was proposed by Berrick et al (2000), who offered a "certificate of achievement" as recognition for children's participation.…”
Section: "Freedom To Participate": Ethical Issues For Strengthening Smentioning
confidence: 99%